Watkins Family Visiting the Graham Family in Berkeley - Watkins, Howard::::::::: (1989)
Good Earth Restaurant and Bakery at 2140 Oxford St. Berkeley (formerly USCA Oxford Hall Co-op and Heavy birthplace)